2019
DOI: 10.1111/opo.12660
|View full text |Cite
|
Sign up to set email alerts
|

Impact of monovision on dynamic accommodation of early presbyopes

Abstract: Purpose To examine the impact of monovision on dynamic changes in accommodation, pupil responses, spherical aberration and resultant image quality in early presbyopes. Methods Refractive state, pupil size and spherical aberration levels were monitored in nine early presbyopes who exhibited some accommodation (40–50 years, mean = 42 ± 2.37 years) using a Shack‐Hartmann aberrometer as a binocularly viewed stimulus stepped closer (from 2 m to 40 cm), or farther (from 40 cm to 2 m). Comparison data from two fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Hayashi et al [26] also found that modified monovision (0.75 D anisometropia) yielded worse near vision than traditional monovision (1.75 D anisometropia). Another possible mechanism proposed by Almutairi et al [30] was that the accommodative response reduced the image quality when the stimulus approached. Presbyopia correction cannot easily yield the best of both far and near vision.…”
Section: Discussionmentioning
confidence: 98%
“…Hayashi et al [26] also found that modified monovision (0.75 D anisometropia) yielded worse near vision than traditional monovision (1.75 D anisometropia). Another possible mechanism proposed by Almutairi et al [30] was that the accommodative response reduced the image quality when the stimulus approached. Presbyopia correction cannot easily yield the best of both far and near vision.…”
Section: Discussionmentioning
confidence: 98%
“…Although micro-monovision studies have been conducted with older LRS techniques such as LASIK or photorefractive keratectomy (PRK) [ 2 ], few studies have been conducted with the combination of SMILE and micro-monovision, mainly because it is a more recent technique [ 6 , 7 , 8 ]. In addition, although the usual clinical practice procedure involves the correction of distance vision in the dominant eye and near vision in the non-dominant eye [ 6 , 7 , 8 ], recent laboratory research suggests that the vision of a patient undergoing a monovision procedure may vary according to different patterns of accommodative response [ 9 ], as presbyopic patients in their 40s and 50s still retain some accommodative capabilities. Thus, depending on the accommodative response, the patient may achieve a different range of clear vision.…”
Section: Introductionmentioning
confidence: 99%